TASYBIH DALAM KITAB QASHIDAH BURDAH KARYA SYAIKH MUHAMMAD IMAM AL BUSHIRI - Iman, Saepul; Hidayat, Deden; Supianudin, Asep (Hijai - Journal on Arabic Language and Literature, 2019)
Kitab Qashidah Burdah is a book authored by Shaykh Muhammad Al Bushiri. This Qashidah in the book tells the story of the story of the Prophet Muhammad, the Apostolic privileges, the Prophet Muhammad, to the miracle. In Verse-verse contained in the book of Qashidah is very beautiful Burdah. Therefore, the very need to be examined, beauty-beauty that exists on the Poetry Book. Qashidah Burdah by using the review Balaghoh Bayan Tasybih Science in particular. The problem in this research include what type of Tasybih in the book Qashidah Burdah works of Shaykh Muhammad Imam Al Bushiri?, and how Tasybih Purpose in the book Qashidah Burdah works of Shaykh Muhammad Imam Al Bushiri?. As for the purpose of this research is to know the type and purpose of Tasybih in the book Qashidah Burdah works of Shaykh Muhammad Imam Al Bushiri. To achieve that goal this research uses descriptive analytic method. Descriptive analytic method is done by means of descript the data in the form of a word or phrase containing Tasybih, then proceed with the analysis. This research uses the study of science science approach with Parrot Balaghah.Â Conclusion of this research is that the Tasybih contained in the book of Qashidah Burdah works of Shaykh Muhammad Imam Al Bushiri 11 types of Tasybih, such as: Tasybih Mursal Mufashshal on get at 4 Temple of poetry, Tasybih Puberty in the get on 2 the Temple of poetry, Tasybih Mursal Mujmal Temple poems on 2, Tasybih Mufashshal Ghoiru Tamtsil Mursal at 2 Temple of poetry, Tasybih Muakkad Mufashshal at 2 Temple of poetry, Tasybih Mursal Mufashshal Tamtsil at 7 Tasybih poetry, Mursal Temple on Temple 5 poems Tasybih Mujmal Temple poems 1 Tasybih, Muakkad Mufashshal Tamtsil at 1 Temple of poetry, and Tasybih Muakkad Mujmal Maqlub 1 Temple, Tasybih Dhimny Temple on 12 verses. The purpose of Tasybih found in: Bayan musyabbah al things in 28 Temple of poetry, Bayan al imkan musyabbah in poetry, Tazyin Temple 3 al musyabbah in the 5th stanza poem, Mengongkritkan musyabbah Temple in three verses, and Bayan miqdar al musyabbah thing in 3 Temple poems